Successful transcatheter aortic valve implantation (TAVI) is associated with transient left ventricular dysfunction. Issue 22 (21st August 2012) - Dworakowski, Rafal; Wendler, Olaf; Bhan, Amit; Smith, Lindsay; Pearson, Peter; Alcock, Emma; Rajagopal, Kailasam; Brickham, Beth; Dew, Tracy; Byrne, Jonathan; Monaghan, Mark J; Sherwood, Roy; et al.
Abstract : Objective: To investigate early haemodynamic changes after transfemoral transcatheter aortic valve implantation (TAVI) and the relationship with myocardial injury and neurohormonal activation. Design: Single-centre prospective observational study. Setting: Tertiary cardiac centre. Patients: 42 patients undergoing transfemoral TAVI were included in this study. Main outcome measures: Haemodynamic measurements and echocardiography-derived indices characterising myocardial function were recorded at baseline, 6 and 24 h postprocedure. Postprocedural myocardial injury was quantified using serum troponin I and CK-MB levels. In addition, biomarkers of myocardial dysfunction/heart failure and neurohormonal activation were measured. Results: 6 h Post-TAVI there was a significant deterioration in both systolic and diastolic function as measured by dP/dtmax /EDV, myocardial performance index and mean E/e' index. Recovery of myocardial function was observed at 24 h. These haemodynamic changes were associated with a significant increase in both troponin I (0.07±0.01 vs 1.59±0.21 μg/l, p<0.005) and CK-MB (1.99±0.19 vs 6.82±0.7 ng/ml, p<0.005). There was a positive correlation among myocardial injury and NT-BNP (r=0.34, p<0.0005), aldosterone (r=0.56, p<0.0001) and ST2 levels (r=0.21, p<0.05). Conclusions: This is the first study to demonstrate that procedurally successful TF-TAVI results in a transient depression of both systolic and diastolic left ventricular function within the first 24 postoperative hours, despite impressive relief of previously severe, chronic pressure overload. The rise in the markers of myocardial damage suggests that this may be due to periprocedural myocardial injury. Complete recovery of contractility is generally observed after 24 h.